Analysis of the Impact of ROE, EPS, CR, and DER Ratio on Stock Return in Automotive Sector Companies Listed on the IDX - Sahat Mangahut Tua; Ratih Kusumawardhani; Johannes Maysan Damanik (PT SOLUSI EDUKASI BERDIKARI, 2025)
This study analyzes the effect of return on equity (ROE), earnings per share (EPS), current ratio (CR), and debt to equity ratio (DER) on stock return in automotive sector companies on the Indonesia Stock Exchange (IDX) from 2016 to 2023. Using a quantitative research approach, this study uses multiple linear regression analysis on a sample of automotive companies to examine the relationship between these financial performance indicators and stock returns. The results indicate that ROE, EPS, CR, and DER each significantly impact stock return. The simultaneous analysis confirms these four variables collectively influence stock return significantly. These findings suggest that investors should consider these financial ratios when making investment decisions in the automotive sector.